2014
DOI: 10.1080/15283488.2014.921170
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Identity Insults: A Social Identity Theory Perspective

Abstract: The purpose of this article is to build a systemic theory of insult based on insights from social identity theory and theories of power. Six types of insult are described: identity, projection, divergence, relative, power, and legitimacy, and the differences among them analyzed. The processes that constitute the dynamics of insult are considered. Following this theoretical analysis, the case of insults connected with the actions of the rock group Pussy Riot in Russia are interpreted in terms of various types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Incivility is a potential means for partisans such as conservatives and liberals to mark themselves as group members. Research applying social identity theory to explain intergroup insults, for example, suggested that directing insults at an outgroup reinforces one's status as an ingroup member (Korostelina, ). If incivility serves as a mechanism for identity consolidation in visually anonymous CMC, then partisans should be more likely to engage in incivility under certain conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incivility is a potential means for partisans such as conservatives and liberals to mark themselves as group members. Research applying social identity theory to explain intergroup insults, for example, suggested that directing insults at an outgroup reinforces one's status as an ingroup member (Korostelina, ). If incivility serves as a mechanism for identity consolidation in visually anonymous CMC, then partisans should be more likely to engage in incivility under certain conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pro-RASIM comments included expressions of support and sympathy for the RASIM plight, and calls for the government to accept more RASIM. The comments were subsequently categorised according to the taxonomy developed by Korostelina (2014) and compared for each group. In quoting from the data, all users’ names are anonymised and original spellings were preserved.…”
Section: Othering Rasimmentioning
confidence: 99%
“…The taxonomy was devised by Korostelina (2014) in her paper analysing insults traded at the time of the Pussy Riot controversy in Russia. It is ‘based on insights from social identity theory and theories of power’ (Folkenflik, 2013) and constitutes ‘proposed theoretical concepts to the analysis of complex conflict dynamics’ (p. 214).…”
Section: Taxonomy Of Insultsmentioning
confidence: 99%
“…Meanings attached to social identity are products of our collective history (Reicher, Spears and Haslam, 2010) because group members enact roles that are part of group's expectations (Turner et al, 1994). Groups give their members a sense of belonging to the social world, a particular social status, protection, security and emotional support (Korostelina, 2014). That is why they are an important source of pride and self-esteem (Tajfel, 1979).…”
Section: Social Identity Theorymentioning
confidence: 99%
“…That is why they are an important source of pride and self-esteem (Tajfel, 1979). Belonging to a certain group means being like other group members and viewing things from the group's perspective (Stets and Burke, 2000;Korostelina, 2014). According to Social Identity Theory, social identity has three main components: a) social categorization; b) social identification; c) social comparison (Tajfel and Turner, 1979).…”
Section: Social Identity Theorymentioning
confidence: 99%